2010
DOI: 10.1111/j.1540-8175.2009.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isolated Obesity on Left and Right Ventricular Function: A Tissue Doppler and Strain Rate Imaging Study

Abstract: The presence and the duration of obesity were associated with impairment of subclinical biventricular systolic and diastolic function. These findings have the potential to increase awareness of subclinical cardiac manifestations in patients with isolated obesity and influence their early management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
64
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 40 publications
10
64
2
3
Order By: Relevance
“…In contrast to the above mentioned results, we and others 17,25,26) have found no association of RV function and increasing BMI in obese and/or overweight persons. Additionally, right atrial and right ventricular end-systolic and diastolic dimensions, as well as RV diastolic function did not differ significantly across increasing BMI categories.…”
Section: Discussioncontrasting
confidence: 43%
See 3 more Smart Citations
“…In contrast to the above mentioned results, we and others 17,25,26) have found no association of RV function and increasing BMI in obese and/or overweight persons. Additionally, right atrial and right ventricular end-systolic and diastolic dimensions, as well as RV diastolic function did not differ significantly across increasing BMI categories.…”
Section: Discussioncontrasting
confidence: 43%
“…Additionally, right atrial and right ventricular end-systolic and diastolic dimensions, as well as RV diastolic function did not differ significantly across increasing BMI categories. 17,25,26) On the other hand, these studies consistently found significant alterations of LV parameters, implying more sensible adaptions of the left than the right heart to increasing adiposity. The reasons for the incongruent study results remain speculative.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies suggested that some factors such as obesity, insulin resistance and age could affect the myocardial strain measurements. Obesity can cause a subclinical impairment in myocardial functions alone (14,15). Insulin resistant people can show subclinic deterioration in myocardial functions (16).…”
Section: Discussionmentioning
confidence: 99%